1978
DOI: 10.1203/00006450-197803000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Catecholamines in Lung Liquid Absorption at Birth

Abstract: SummaryWe have examined the effect on lung liquid secretion of catecholamines ipfused in chronically catheterized fetal lambs in utero. Isoproterenol and epinephrine inhibited secretion, an effect which increased with gestation and, in fetuses near delivery, caused absorption of lung liquid. In 7 out of 8 experiments nor-epinephrine had no effect on secretion. This pattern of response and the fact that the inhibitory effect could

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
2
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(192 citation statements)
references
References 0 publications
8
179
2
3
Order By: Relevance
“…Walters and Olver 19 demonstrated that both epinephrine and isoproterenol, but not norepinephrine, infused intravenously into chronically catheterized mature fetal sheep, caused rapid absorption of lung liquid that could be inhibited by previous treatment with propranolol. Moreover, the effect of epinephrine on fetal lung fluid secretion was further studied by Lawson et al,20 who demonstrated that epinephrine infused into fetal sheep resulted in a decrease in tracheal flow.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…Walters and Olver 19 demonstrated that both epinephrine and isoproterenol, but not norepinephrine, infused intravenously into chronically catheterized mature fetal sheep, caused rapid absorption of lung liquid that could be inhibited by previous treatment with propranolol. Moreover, the effect of epinephrine on fetal lung fluid secretion was further studied by Lawson et al,20 who demonstrated that epinephrine infused into fetal sheep resulted in a decrease in tracheal flow.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
“…21 Subsequent studies demonstrated that intraluminal administration of amiloride, a Na þ -transport inhibitor, blocked the effect of epinephrine on absorption of lung fluid, indicating that the lung liquid absorption is dependent on epinephrine-evoked Na þ transport. 19,22 At birth, the lungs must clear their fluid rapidly to enable a normal transition from intrauterine liquid breathing to postnatal air breathing. To do so, the lung has to convert quickly and efficiently from a fluid secreting to a fluid-absorbing organ.…”
Section: Lung Fluid During and Immediately After Birthmentioning
confidence: 99%
“…26 In a sheep model, infusion of epinephrine, a catecholamine hormone, decreased secretion and promoted the absorption of fetal lung fluid. [27][28][29][30] Despite substantial evidence linking catecholamine hormones with TTN, no prior study in humans has examined the use of exogenous catecholamines for the treatment of TTN. Epinephrine is a catecholamine hormone available in systemic and inhaled form.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure was similar to those described by Normand et al (1970) and Walters & Olver (1978). By following the changes in the indicator concentration, after a 30 min mixing period, the rate of lung liquid production or absorption can be calculated.…”
Section: Lung Liquid Volume Estimation Techniquementioning
confidence: 99%
“…Preparation of the fetuses was similar to that described by Walters & Olver (1978) and Brown et al (1983). Briefly, pregnant ewes (Suffolk-Clun Forest cross) were operated on between 118 and 125 days from conception (term, 147 days).…”
mentioning
confidence: 99%